The Impact of Adverse Childhood Experiences on Adulthood Aggression and Self-Esteem-A Study on Male Forensic Clients - Khodabandeh, Farideh; Khalilzadeh, Marzieh; Hemati, Zahra (Novelty in Biomedicine, 2018)
Background: Adverse childhood experiences (ACEs) are stressful or traumatic events, including abuse and neglect. The long-term effects of adverse childhood experiences (ACEs) occurring during childhood or adolescence; may lead to a wide range of physical and psychological health issues throughout a person’s lifespan. Children with ACEs, develops poor relation skills and low self-esteem, which may increase the likelihood of interpersonal problems and physical aggression in adult life. The current study examined the correlation among adverse childhood experiences (ACEs), self-esteem, and aggressive behavior. Materials and Methods: The sample included 350 adult male clients, accused of physical aggression in forensic setting. All participants completed interviews, focusing on different types of maltreatment prior to age 18, using the modified standardized Adverse Childhood Experiences International Questioner (ACE-IQ) and self-esteem level by Rosenberg Self-esteem Scale. Results: The most commonly reported adverse experience was family dysfunction, mainly violence in the family that caused problems. Strong correlations were shown to exist between various ACEs and aggressive behavior. Negative correlation detected between self–esteem and all categories subjected for ACE except sexual abuse and community violence (P=0>.05). Conclusion: Much attention has been focused on adverse childhood experiences as risk factors for a spectrum of violence-related outcomes during adulthood.